Response of yearling steers on bluestem pastures that were intensively stocked early in season - L.L. Berger; L.H. Harbers; R.R. Schalles; E.F. Smith; Clenton E. Owensby (Kansas Agricultural Experiment Station Research Reports, 1974)
Nine pastures of 492 acres were summer grazed by yearling steers. Five were burned April 24, 1973; four were not burned. Burned and nonburned pastures had 0, 40, or 80 lbs. of nitrogen per acre applied aerially. Stocking rates were determined with herbage production data from experimental plots under similar treatments. Under the same fertilization and stocking rates, average daily gain and gain per acre were higher for burned pastures than nonburned pastures. Fertilizing bluestem tended to reduce daily gains but increased gain per acre. Steers on the early-season, intensively grazed pasture, gained the most per day (1.51 lbs) and produced one of the higher per-acre gains (72 lbs.).
Keywords: Cattlemen' s Day; 1974; Report of progress (Kansas State University. Agricultural Experiment Station); 210; Beef; Steers; Bluestem; Stocking rates; Gain